2022
DOI: 10.1111/cas.15585
|View full text |Cite
|
Sign up to set email alerts
|

NUSAP1, a novel stemness‐related protein, promotes early recurrence of hepatocellular carcinoma

Abstract: Early recurrence (within 2 years after resection) is the primary cause of poor outcomes among hepatocellular carcinoma (HCC) patients, and liver cancer stem cells are the main contributors to postsurgical HCC recurrence. Nucleolar and spindle‐associated protein 1 (NUSAP1) has been reported to be involved in tumor progression. We investigated the function and clinical value of NUSAP1 in early recurrence of HCC. Data from public datasets and our cohort were used to assess the association between NUSAP1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In breast cancer, NUSAP1 has been associated with poor overall survival and infiltration of various immune cells [ 17 ]. Moreover, in HCC, increased NUSAP1 expression has been linked to a poor prognosis, particularly early recurrence, and has been shown to facilitate early recurrence of HCC [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, NUSAP1 has been associated with poor overall survival and infiltration of various immune cells [ 17 ]. Moreover, in HCC, increased NUSAP1 expression has been linked to a poor prognosis, particularly early recurrence, and has been shown to facilitate early recurrence of HCC [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In CHB patients, a wider range of immune cells was observed to infiltrate. Our hypothesis is that this may be linked to the reported biological function of NUSAP1 in enhancing tumor stemness [ 18 , 19 ]. NUSAP1 knockout decreased the expression of surface markers of cancer stem cells (CSCs), and NUSAP1 was highly expressed in self-renewing CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that NUSAP1 was significantly associated with worse prognosis and early postoperative recurrence of HCC patients. Mechanistic study showed that NUSAP1 increased the likelihood of HCC early recurrence in murine model by promoting cancer stemness via STAT3/RACK1 pathway 161 . Similarly, Abelson interactor 2 was identified to drive HCC recurrence by activating cancer stemness‐related pathway 162 …”
Section: Tme Alternations After Surgery: Potential Triggers For Hcc R...mentioning
confidence: 99%
“…Mechanistic study showed that NUSAP1 increased the likelihood of HCC early recurrence in murine model by promoting cancer stemness via STAT3/RACK1 pathway. 161 Similarly, Abelson interactor 2 was identified to drive HCC recurrence by activating cancer stemness-related pathway. 162…”
Section: Stem-like Cell: Driving Force For Intrahepatic Recurrence An...mentioning
confidence: 99%
“…Owing to the development of radiological techniques and serological detection capabilities, noninvasive prediction of postoperative recurrence has become possible. Although radiology techniques (artificial intelligence, radiomics) or serologic markers (mortalin, nucleolar, and spindle-associated protein 1) are used to predict recurrence (13)(14)(15)(16), artificial intelligence and radiomics are complex and difficult to master and serologic markers change dynamically. Studies combining the two techniques are extremely rare.…”
Section: Introductionmentioning
confidence: 99%